Abstinence from Ngalor Ngetan Marriage in Dempel Village, Karangrayung Subdistrict, Grobogan Regency from the Perspective of 'Urf - Ahmad Haidar Zakiyul Fuad (Pusat Studi Penelitian dan Evaluasi Pembelajaran, 2023)
In Javanese society there are traditions that are very thick and are believed to this day. One of the customs that is still applied today is the abstinence from ngalor ngetan marriage, although this tradition is prohibited but the development of the times the community ignores what traditions have been prohibited by the predecessors. This becomes a dilemma because it is considered to cause or bring unwanted things to the two families. This article wants to reveal how the practice of abstinence from ngalor ngetan marriage. Secondly, how is the 'urf review of the abstinence from ngalor ngetan marriage. The research used in this study is field research. The method used in this research is qualitative research. This research also uses collection methods in the form of documentation and interview methods which are then analyzed by qualitative descriptive methods. The results of the study state that: ngalor ngetan marriage in Dempel Village, Karangrayung District, Grobogan Regency is a tradition that in my opinion has challenged the abstinence of ngalor ngetan marriage which has been applied since ancient times, although now with the passage of time some of the people of Dempel Village have ignored the abstinence. The community's perception of ngalor ngetan marriage in terms of 'urf, the author categorizes the tradition in Dempel Village marriages as 'urf amali and falls into the category of 'urf that is not valid because there are several conditions and pillars that are not in line with Shari'ah.